Cuba in a global context : international relations, internationalism, and transnationalism - Krull, Catherine; Pérez, Louis A., 1943- (Contemporary Cuba, 2014)
Examines the relationships between post-revolutionary Cuba and other nations across the globe, providing case studies within the themes of international relations, internationalism, and transnationalism.